2005
DOI: 10.1148/rg.25si055509
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vascular Malformations: Imaging, Treatment Approaches, and Therapeutic Issues

Abstract: Peripheral vascular malformations are now described according to some accepted guidelines, and the principle of proper treatment (nidus ablation) is becoming clear. An appropriate classification scheme for vascular anomalies and definite indications for treatment are important to successful treatment overall. The findings from noninvasive imaging (ie, Doppler ultrasonography, computed tomography, or magnetic resonance imaging) in association with clinical findings are critical in establishing the diagnosis, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(166 citation statements)
references
References 36 publications
1
151
0
14
Order By: Relevance
“…In addition, NBCA has been indicated for arterial redistribution and hepatic arterial catheter fixation during hepatic arterial infusion chemotherapy [68,159,180,181]. In the venous system, retrospective studies examining the use of NBCA for percutaneous transhepatic portal venous embolization have also been reported [19,45,48,49,77], and there have been several studies about the use of NBCA for pelvic congestion syndrome and varicoceles [27,65,109,157].…”
Section: International Situationmentioning
confidence: 99%
“…In addition, NBCA has been indicated for arterial redistribution and hepatic arterial catheter fixation during hepatic arterial infusion chemotherapy [68,159,180,181]. In the venous system, retrospective studies examining the use of NBCA for percutaneous transhepatic portal venous embolization have also been reported [19,45,48,49,77], and there have been several studies about the use of NBCA for pelvic congestion syndrome and varicoceles [27,65,109,157].…”
Section: International Situationmentioning
confidence: 99%
“…Ohgiya et al measured the time interval between the onset of enhancement and maximum percentage of enhancement in the lesion, the so-called "contrast rise time" (CRT). They showed that LFVM presented a mean contrast rise time of 88 s. A CRT threshold of 30 s was set, guaranteeing 100% specificity and sensitivity in the differentiation of low-flow from high-flow VMs [2,7]. Sclerotherapy is the mainstay of treatment; it is based on the injection of an agent (commonly absolute ethanol) to induce an inflammatory reaction and obliteration of the affected veins.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotherapy is the mainstay of treatment; it is based on the injection of an agent (commonly absolute ethanol) to induce an inflammatory reaction and obliteration of the affected veins. Selected cases should undergo surgical resection later [2] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Hyodoh H et al reported excellent results with sclerotherapy in 53%-100% patients. 22 According to Lee BB et al, success rates using absolute alcohol have been reported in up to 95% with no evidence of recurrence. 23,24 Results In comparison to hemangiomas, vascular malformations diagnosed at birth shows no signs of involution with age and might expand close to puberty.…”
Section: Treatmentmentioning
confidence: 99%